Answer:
It looks like you forgot to attach a picture.
Since I cannot answer you're question fully, it will not be a complete solution.
The formula for the area of a triangle is
.
Just substitute you're base and height values.
Hope this helps!!!
Answer:
a.) 4/6
Step-by-step explanation:
3/5 = .6
<u><em>4/6 = .666666666667</em></u>
6/12= 0.5
3/8= .375
4/10= .4
Answer:
Step-by-step explanation:
Given that
Area of a circle ![A=\pi r^2](https://tex.z-dn.net/?f=A%3D%5Cpi%20r%5E2)
Circumference of the circle ![C = 2 \pi r](https://tex.z-dn.net/?f=C%20%3D%202%20%5Cpi%20r)
Let us re-write the equation of area of circle:
![A=\pi r^2](https://tex.z-dn.net/?f=A%3D%5Cpi%20r%5E2)
![A = \pi \times r \times r](https://tex.z-dn.net/?f=A%20%3D%20%5Cpi%20%5Ctimes%20r%20%5Ctimes%20r)
Multiplying and dividing with 2:
![A = \dfrac{2\pi r}{2} \times r\\\text{Putting }2\pi r = C:\\\Rightarrow A = \dfrac{C}{2} \times r\\\text{Multiplying and dividing by } 2\pi:\\\Rightarrow A = \dfrac{C}{2} \times \dfrac{2\pi r}{2\pi}\\\text{Putting }2\pi r = C:\\\Rightarrow A = \dfrac{C \times C}{4 \pi}\\\Rightarrow A = \dfrac{C^2}{4 \pi}](https://tex.z-dn.net/?f=A%20%3D%20%5Cdfrac%7B2%5Cpi%20r%7D%7B2%7D%20%5Ctimes%20r%5C%5C%5Ctext%7BPutting%20%7D2%5Cpi%20r%20%3D%20C%3A%5C%5C%5CRightarrow%20A%20%3D%20%5Cdfrac%7BC%7D%7B2%7D%20%5Ctimes%20r%5C%5C%5Ctext%7BMultiplying%20and%20dividing%20by%20%7D%202%5Cpi%3A%5C%5C%5CRightarrow%20A%20%3D%20%5Cdfrac%7BC%7D%7B2%7D%20%5Ctimes%20%5Cdfrac%7B2%5Cpi%20r%7D%7B2%5Cpi%7D%5C%5C%5Ctext%7BPutting%20%7D2%5Cpi%20r%20%3D%20C%3A%5C%5C%5CRightarrow%20A%20%3D%20%5Cdfrac%7BC%20%5Ctimes%20C%7D%7B4%20%5Cpi%7D%5C%5C%5CRightarrow%20A%20%3D%20%5Cdfrac%7BC%5E2%7D%7B4%20%5Cpi%7D)
Hence, <em>A</em> in terms of <em>C</em> can be represented as:
![A = \dfrac{C^2}{4\pi}](https://tex.z-dn.net/?f=A%20%3D%20%5Cdfrac%7BC%5E2%7D%7B4%5Cpi%7D)
The answer of your question is x - 4 y=8
Answer: Choice D) 5
-----------------------------------------------------------
-----------------------------------------------------------
Notice the hole at (1,2). This means x = 1 and y = 2
y = f(x)
y = f(1) after we replace x with 1
y = 2
If we go from f(x) to f(x-4), then we shift the xy axis four units to the left. The curve will stay still though it will move relative to the xy axis. The xy axis moves four units to the left, so it appears that the curve moved 4 units to the right.
Add 4 to the x coordinate:
x = 1 ---> x+4 = 1+4 = 5
The y coordinate stays the same. No vertical shifting is done.
So we go from (1,2) to (5,2)
(1,2) is a hole on y = f(x)
(5,2) is a hole on y = f(x-4)
This is why the answer is x = 5